2009
DOI: 10.1080/15438620903352057
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Joint Stiffness in Runners with Low Back Pain

Abstract: The purpose of this retrospective study was to examine lower extremity joint stiffness between runners with and without low back pain. We compared data from three groups: current low back pain (LBP), resolved pain (RES), and a control (CTRL) group of runners. We hypothesized that the LBP group would exhibit increased ankle, knee, and hip joint stiffness when compared with the other groups. Subjects ran on a force treadmill at 3.8 m*s(-1) while data were collected. Joint stiffness was determined from the joint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 18 publications
2
45
1
1
Order By: Relevance
“…Kinetic variables included the peak moments and joint stiffness [29] [k j , Equation (1)] of hip, knee and ankle the vertical stiffness of the lower extremity [30] [k vert , Equation (2)], and they were expressed as follows:…”
Section: Statisticsmentioning
confidence: 99%
“…Kinetic variables included the peak moments and joint stiffness [29] [k j , Equation (1)] of hip, knee and ankle the vertical stiffness of the lower extremity [30] [k vert , Equation (2)], and they were expressed as follows:…”
Section: Statisticsmentioning
confidence: 99%
“…For example, SSC effectiveness improves with training [26], and deteriorates in the presence of overuse injuries. Whilst SSC dysfunction has been demonstrated in several overuse conditions [20,35,38], due to its intimate relationship with the SSC, the condition that has received the most attention is Achilles tendinopathy (AT) [14,33,41]. An important physiological phenomenon that links SSC effectiveness and injury is fatigue.…”
Section: Introduction ▼mentioning
confidence: 99%
“…Furthermore, considering that all subjects were healthy, caution should be taken when relating these results to a population with LBP. It has been reported that individuals with LBP display different trunk, pelvis, and lower extremity kinematics compared to healthy individuals (30)(31)(32)(33)(34). While the participants of our study displayed limited passive hip extension similar to individuals who suffer from LBP, they were otherwise a healthy population.…”
Section: Limitationsmentioning
confidence: 59%